Volume restoration of hands with polycaprolactone by cannula delivery; a prospective single center consecutive case series evaluation. (17th February 2020) - Lowe, Nicholas J.; Ghanem, Ali M.
ABSTRACT: Background : Dorsal hand volume loss results in the perception of aging appearance. Several volumizing fillers have been used for this correction. Objective : To report restoration of dorsal hand volume using cannula delivery of Polycaprolactone (PCL) microspheres and to assess efficacy, duration, and safety up to 3 years post treatment. Method : Fifteen patients with volume loss of their hands were evaluated by clinical examination, photography and a hand volume grading scale. PCL was injected by 25 G cannula after locating dorsal veins using a viewing laser to avoid intravascular injections. Patients' satisfaction and grade of severity were reevaluated at early (3–6 months) and late (12–18 months) timepoints following the procedure. A second treatment was offered if desired by the patient. Results : Eight participants required one treatment session to achieve satisfaction. Five had two treatments. Patients requiring a second treatment were reassessed after 12 months. All patients had improvements on the severity score by the end of the evaluation period. Side effects were minimal and transient. No patients developed bruising. Conclusion : PCL injections are reliable method for hand volumization. Results persisted for up to 3 years in some patients. Laser vein viewer and cannula delivery ensure uniform injections and avoid intravascular injuries.